PENGARUH GAME BASED LEARNING BERBANTUAN MPA'A NCIMI TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS II SD - Rini Fitrianingsih; Adi Apriadi Ardiansyah; Haris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning interest among Indonesian elementary school students remains low, including second-grade students at SDN Rada, who show difficulty understanding multiplication, avoid memorization activities, and learn in a passive classroom due to conventional teaching. This problem is worsened by the lack of local-wisdom-based educational games, such as the traditional mpa'a ncimi game, which has the potential to increase student participation and learning interest. This study aims to determine the effect of the Game Based Learning (GBL) model assisted by the traditional mpa'a ncimi game on the mathematics learning interest of second-grade students at SDN Rada. A quantitative approach was used with a One Group Pretest–Posttest pre-experimental design involving 17 second-grade students as a saturated sample. Data were collected using a four-point Likert scale questionnaire tested for reliability (Cronbach's α = 0.987) and analyzed using a paired sample t-test and Cohen's d effect size test. Results showed an increase in the average learning interest score from 62.5 (pretest) to 73.6 (posttest), with a t-test result of -30.7 (df = 16; p < 0.001) indicating a significant difference, and a Cohen's d of 7.44 categorized as a very large effect. Based on posttest categorization, 11 students (64.7%) fell into the Medium category and 3 (17.6%) into the High category. It can be concluded that the GBL model assisted by the traditional mpa'a ncimi game significantly increases mathematics learning interest among second-grade students at SDN Rada, and serves as an alternative contextual, local-culture-based learning strategy for schools with limited technological facilities.